Auf den Spuren von Anton Wilhelm Amo: Philosophie und der Ruf nach Interkulturalität - Hofmann, Tim; Eberhard, Jens; Wolfradt, Louis; Knauß, Stefan (transcript, 2021)
Is the decolonization of philosophy possible? The African philosopher of enlightenment Anton Wilhelm Amo in the light of intercultural philosophy.